Using survey data to assess the distributional effects of trade policy - Porto, Guido Gustavo (2006)
This paper develops a method to estimate the general equilibrium distributional effects of trade policies using household survey data. Trade reforms cause the domestic prices of traded goods to change and this, in turn, triggers a series of general equilibrium effects. Among these, I estimate the impacts of trade on the prices of traded goods, non-traded goods, and wages. By combining the estimates of the consumption impacts and the labor income impacts, I am able to assess how trade policies affect households across the entire range of the income distribution. An application of the procedure to the study of the distributional effects of Mercosur shows that the average poor and middle-income family in Argentina has benefited from the trade agreement.